Acute Sildenafil Use Reduces 24‐Hour Blood Pressure Levels in Patients With Resistant Hypertension: A Placebo‐Controlled, Crossover Trial. Issue 11 (1st June 2016) - Santa Catharina, Arthur; Modolo, Rodrigo; Ritter, Alessandra Mileni Versuti; Quinaglia, Thiago; de Amorim, Rivadávio Fernandes Batista; Moreno, Heitor; de Faria, Ana Paula
Abstract : The authors previously demonstrated that acute administration of sildenafil—a phosphodiesterase 5 (PDE5) inhibitor—improves hemodynamic parameters in patients with resistant hypertensive (RH), but its effect on ambulatory blood pressure monitoring (ABPM) is unknown. This interventional, nonrandomized, single‐blinded, placebo‐controlled, crossover trial included 26 patients with RH. A dose of sildenafil (187.5mg) was given, and after a washout period of 14 days the patients received a single oral dose of placebo and the protocol was repeated. The patients underwent 24‐hour ABPM recordings the day before and immediately after the protocols. The reduction of systolic (−8.8±1.4 vs 1.3±1.2 mm Hg, P =.02), diastolic (−5.3±3.3 vs 1.8±1.1 mm Hg, P =.03), and mean (−7.9±3.6 vs 0.8±0.9 mm Hg, P =.01) 24‐hour BP were found after the use of sildenafil compared with placebo. Improvement in daytime BP levels was also observed (systolic −6.0±4.7 vs 4.4±1.5 mm Hg [ P =.02] and mean −4.8±3.9 vs 3.5±1.4 mm Hg [ P =.02] for sildenafil vs placebo, respectively). Considering its antihypertensive effect, sildenafil may represent a therapeutic option for RH treatment.